Author Correction: Molecular patterns of isolated tubulitis differ from tubulitis with interstitial inflammation in early indication biopsies of kidney allografts - Petra Hruba (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.